(untitled) (Canadian Journal of Emergency Management, 2022)
Spurred by the climate crisis, disasters are growing in frequency and severity around the world. In Western Canada, the impacts of the 2013 floods, 2016 wildfires, and the Covid-19 pandemic have devastated communities. Social workers, and human service professionals who assist in meeting the needs of individuals, families, groups, and communities in overcoming challenges, such as education assistants, outreach workers, and child and family support workers, are increasingly involved in the mitigation, preparedness, response, and recovery phases of disasters. However, their role is not always visible or understood by emergency management professionals. Social work is a practice-based profession that responds to the needs of individuals, families, groups, and communities, and addresses barriers and injustices in organizations and society. This article shares the findings of the study “In the aftermath of the 2016 Alberta wildfires: The role of social work practitioners and human service professionals in long-term disaster recovery.” The study adopted a mixed-method research approach that recruited 140 participants to share their experiences in semi-structured interviews, an online survey, and focus groups. A thematic analysis of the data found that social workers and human service practitioners play many critical roles in disaster recovery. This includes advocacy, assessment, counselling, crisis intervention, trauma informed care, peer support, community development, providing services and programs, research, supporting first responders. Social workers can also provide valuable input into other disaster phases. For example, social workers are embedded in communities and have relationships with residents that can inform emergency plans. They provide emergency professionals insight into the needs of residents and bring collaboration skills that enhance preparedness and mitigation programs. The study findings call for greater recognition of the role of social workers and human service professionals in disasters by emergency management professionals. Implications and recommendations for social work and emergency management professionals are offered to facilitate interdisciplinary collaboration.